2015
DOI: 10.5751/es-07390-200168
|View full text |Cite
|
Sign up to set email alerts
|

Sharing as risk pooling in a social dilemma experiment

Abstract: ABSTRACT. In rural economies with missing or incomplete markets, idiosyncratic risk is frequently pooled through informal networks. Idiosyncratic shocks, however, are not limited to private goods but can also restrict an individual from partaking in or benefiting from a collective activity. In these situations, a group must decide whether to provide insurance to the affected member. We describe results of a laboratory experiment designed to test whether a simple sharing institution can sustain risk pooling in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Thus, donations from the outgroup were more than enough to compensate for the loss of resources because of shocks. These results are in line with the findings from Cherry et al (2015). The authors showed that individuals are willing to compensate losses to other group members in the presence of idiosyncratic risk.…”
Section: Results 4 the Possible Explanations Of The High Frequency Osupporting
confidence: 82%
See 1 more Smart Citation
“…Thus, donations from the outgroup were more than enough to compensate for the loss of resources because of shocks. These results are in line with the findings from Cherry et al (2015). The authors showed that individuals are willing to compensate losses to other group members in the presence of idiosyncratic risk.…”
Section: Results 4 the Possible Explanations Of The High Frequency Osupporting
confidence: 82%
“…My work also relates to the literature on risk pooling within groups, which I expand to the intergroup context. Recently, Cherry et al, (2015) examined whether subjects are willing to share their payoffs with other members of their group who lost some endowments because of the idiosyncratic shock. The authors report high levels of intragroup sharing, which reduce the variance of individual earnings.…”
Section: Introductionmentioning
confidence: 99%
“…Individual cash earnings were determined by a single round that was randomly selected by a die roll at the end of the experiment [ 10 , 43 ]. Selecting a single round eliminated the possibility for participants to pool earnings over time, which would have been analogous to individually insuring against shocks.…”
Section: Methodsmentioning
confidence: 99%
“…However, cooperation often occurs in multiple domains. In addition to contributing to the public good or harvesting from a shared resource, what we refer to as the “production domain,” cooperation can also emerge in other domains, such as punishing defectors [ 3 6 ], rewarding cooperators [ 7 9 ] or sharing with those who experience a hardship [ 10 ]. These domains often interact which reflects the fact that benefits of cooperation can extend beyond a single period, domain, or state of nature [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The groups had higher levels of collective action when risks were higher. Cherry et al (2015) studied the effect of shocks on the willingness of participants to share resources with the affected individual. The experiment was inspired by many situations in Arctic communities where individuals can lose their resource because of external events.…”
mentioning
confidence: 99%